Anthropometry influence on speed and agility among adolescence hockey players / Mohamad Syafwan Mukmin Kharahab - Kharahab, Mohamad Syafwan Mukmin (Faculty of Sports Science And Recreation, Universiti Teknologi MARA, 2019)
The purpose of this study was to identify the correlation of anthropometry on speed and agility among adolescence hockey player. A total of thirty subjects (N=30) age range from 13 to 17 years old (M= 15.47 SD=1.48) were involved in this study and selected through purposive sampling method. The study identified the correlation between speed and agility performance using the 30-meter sprint test and Illinois agility test. Pearson r correlation coefficient was used as this study is to find the correlation between variables. During this study, sample performs one trial of each test being given. The rest between tests is three minutes. Based on the Pearson r Correlation, the result shows that there is no significance between weight and speed (0.27) while height and speed, there was a significant effect (0.001). In other result weight and agility have no significance (0.18) while height and agility have significant (0.006). To conclude, this finding anthropometry does not play a big role on speed and agility of SMK Sulaiman hockey players.